The Tourist Product and its Evolution - Kaczmarek, Jacek; Stasiak, Andrzej; Włodarczyk, Bogdan (Turyzm/Tourism, 2001)
The main objective of the article is to discuss issues concerning the ‘tourist product’ and its historical evolution and the authors attempt to shed new light on the development of tourist flows and tourist services. The discussion is based on the four specific categories of tourist product (ancient, university, industrial and global with special attention paid to the non-historical character of tourist flows motivated by religion and health. In the summary development trends in tourism are pointed to, in particular the benefits and hazards for tourist areas.